Galsworthy: The Social Crusader: Exploring Galsworthy's Artistic Conscience in Socially-Charged Dramas (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In his dramas, as distinct from his novels, Galsworthy has evolved as an individual different from that of the Forsytes and his artistic conscience finds a distinctive expression in them. His dramas are avowed attempts at realistic portrayal of modern society. His presentation and criticism of social questions earned him, at the beginning of this century, the reputation of being a powerful realist, social dramatist of England.Marrot holds that Dickens and Galsworthy were “kindred” spirits, for John Galsworthy, as passionately as Charles dickens, hated, “crookedness, custom and fear. He had within him the true spirit of crusaders.